2021
DOI: 10.1002/jcp.30309
|View full text |Cite
|
Sign up to set email alerts
|

Methylome and transcriptome profiling revealed epigenetic silencing of LPCAT1 and PCYT1A associated with lipidome alterations in polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine diseases of fertile women and a major cause of infertility. The regulatory effects of DNA methylation on gene transcription and downstream lipid metabolism have not been explored in PCOS. In this study, MBD-seq and RNA-seq were performed on ovarian granulosa cells of PCOS patients and controls, and methylation specific PCR and quantitative polymerase chain reaction were used to validate the results. Then lipidomic profiling was conducted on serum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Glycerophospholipids are the most abundant phospholipids in the human body and are involved in membrane protein recognition and signal transduction, and are associated with various metabolic diseases, such as cardiovascular diseases, hypertension, diabetes, obesity, nervous system diseases, etc. [ 34 , 35 ]. One key difference between copper sulfate and Tri is that Cu 2+ accumulates in tissues [ 36 ], which means that the concentration of Cu 2+ in zebrafish increases after each water change.…”
Section: Discussionmentioning
confidence: 99%
“…Glycerophospholipids are the most abundant phospholipids in the human body and are involved in membrane protein recognition and signal transduction, and are associated with various metabolic diseases, such as cardiovascular diseases, hypertension, diabetes, obesity, nervous system diseases, etc. [ 34 , 35 ]. One key difference between copper sulfate and Tri is that Cu 2+ accumulates in tissues [ 36 ], which means that the concentration of Cu 2+ in zebrafish increases after each water change.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 , 29 ] We find LPCAT1 is under direct control of NRF1, thus provide the evidence of transcriptional regulation of LPCAT1 for the first time. We did not analyze lipidomic change by mass spectrometry upon silencing NRF1 in our investigation, but considering the unequivocal regulation of NRF1 on LPCAT1 transcription and the explicit effect of LPCAT1 on PC metabolism,[ 16 , 30 , 31 ] we believe NRF1 could alter phospholipid metabolism in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al identified molecular mechanisms and the novel therapeutic target of late‐onset Alzheimer's disease based on integrating the whole genome and transcriptome 20 . By combining transcriptome and methylome analysis, Zhao et al identify many new ceRNA axes in granulosa cells were associated PCOS, 21 and Mao et al revealed epigenetic silencing of LPCAT1 and PCYT1A associated with lipidome alterations in PCOS 22 …”
Section: Introductionmentioning
confidence: 99%
“…20 By combining transcriptome and methylome analysis, Zhao et al identify many new ceRNA axes in granulosa cells were associated PCOS, 21 and Mao et al revealed epigenetic silencing of LPCAT1 and PCYT1A associated with lipidome alterations in PCOS. 22 Given the genetic and metabolic characteristics of PCOS, it is essential to systematically integrate gene/ protein (indicating both genetic regulation and environment) 18 and metabolites (reflecting phenotype under the regulation of gene/protein) analysis to reveal new PCOSassociated signatures. 23 Recently, some multi-omics studies of combining transcriptomic and metabolomic have identified differentially expressed molecular signatures in whole blood and follicular fluid to investigate the regulatory mechanism of PCOS.…”
Section: Introductionmentioning
confidence: 99%